The development of cadastral database selection application to support modern cadastral and Malaysian spatial data infrastructure - Abdullah Hisam Omar, 1989- 638695; Universiti Teknologi Malaysia. Research Management Centre 3591 (Skudai : Universiti Teknologi Malaysia, 2006)
Includes bibliographical references